Establishment and Long-Term Culture of Organoids Derived from Human Biliary Tract Carcinoma - Saito, Yoshimasa (STAR Protoc, 2020)
This protocol is a procedure for establishment and culture of cancer and non-cancer organoids using tissues from biliary tract carcinoma (BTC) patients. These BTC organoids can be used for various biological analyses and drug screening. One challenge in establishing and culturing BTC organoids is non-cancer cells contaminating surgically resected tumor tissues form organoids concurrently with cancer organoids. Careful validation that the established organoids are cancer-derived is important. For complete details on the use and generation of this protocol, please refer to Saito et al. (2019) in the journal Cell Reports.